BLENDED LEARNING IN STRUCTURE FOR TOEFL® SUBJECT: HOW THE ONLINE MODE SUPPORTS THE ONSITE LEARNING EFFECTIVELY - John Pahamzah; Rahman Hakim (Journal of English Language Teaching and Literature (JELTL), 2019)
This article discusses about the onsite and online mode of learning processes experienced by the students in structure for TOEFL® Subject. It is a case study that aimed to describe how the lecturer prepared the online mode effectively in supporting the onsite learning of the subject. It figured out how the lecturer inventarized the problems found in structure section of TOEFL, and how the students interact with the materials in the online mode.